Effect of extrusion on the phenolic composition and antioxidant activity of dry beans of Phaseolus vulgaris L. - Korus, Jaroslaw (Array, 2007)
The phenolic composition of dry beans and extrudates was investigated to evaluate the effect of extrusion process on their antioxidant activity. Myricetin, quercetin, kaempferol, cyanidin, chlorogenic acid, caffeic acid, ferulic acid and p-coumaric acid were identified in raw and processed bean seeds. The effect of extrusion on the total phenolic content of beans depended on the cultivar – one variety showed a 14 % increase in the amount of phenolics in extrudates compared to raw beans, while the other two exhibited a decrease by 19 and 21 %. Extracts from bean extrudates showed a faster initial free radical scavenging activity than the extracts from raw beans; however, the final values were similar. The least active extrudates were obtained by using the initial moisture of 20 % and the temperature of 180 °C. Extrusion also decreased the antioxidant activity, compared to the raw material